Suicidal risk in patients diagnosed with central nervous system tumors – current state of knowledge: Comprehensive review - Skalska-Dziobek, Nina; Naruszewicz, Maria; Midro, Aleksandra; Cetnarowski, Przemysław; Zagórski, Karol; Kozik, Mateusz; Małagocka, Weronika; Chybowska, Karolina (Quality in Sport, 2024)
Introduction and objective: Central nervous system (CNS) tumors, particularly brain tumors, significantly impact mental health, leading to conditions like depression, anxiety, and suicidality. This study examines the prevalence and risk factors for these disorders in CNS tumor patients, focusing on brain tumors. Material and methods: A comprehensive review was conducted to assess suicidality and prevalence of various mental diseases in patients with CNS tumors, focusing on brain tumors. Studies were identified through PubMed, Embase, and Google Scholar, including research on CNS tumors and associated mental health conditions. Key outcomes examined included depression, anxiety, and suicidality. State of knowledge: Gliomas and glioblastomas are strongly linked to mental health challenges, with depression and anxiety being most common. Suicidality is notably higher in CNS tumor patients, influenced by tumor-related neurological and functional impairments. Despite this, mental health care integration into neuro-oncology remains inadequate. Conclusions: CNS tumor patients are at high risk for mental health disorders and suicidality, highlighting the need for early intervention and multidisciplinary care. Better integration of mental health support can improve patient outcomes and quality of life.